Potensi Ekonomi Kreatif Tahun 2024 Negara Indonesia - Rozikin Rozikin; Mohammad Jon Tasrif (Jurnal Manajemen FE-UB, 2023)
The development of information and communication technology and the internet, which has been unexpectedly accelerated by the presence of a pandemic, has instantly changed social and economic life. The era of Industrial Revolution 4.0 brought digital transformation into economic and societal life and gave birth to a digital economy. Problems in Indonesia in dealing with the digital economy include starting from the licensing process and granting business licenses which are still running slowly, until the efficiency of the supply chain system and value chain of digital products has not been achieved. Indonesia's strengths in building a digital economy range from the development of ICT and internet infrastructure to funding for Indonesian start-ups, which have reached 2,300 companies. The additional value of creative economy exports is equivalent to 15.54 trillion rupiah. By analyzing the input output table for the creative economy, the result is that the additional creative economy exports of 15.54 trillion rupiahs will provide an additional creative economy GDP of 7.81 trillion rupiahs. This causes the growth of the creative economy in 2024 to be 0.71 percent. However, the growth of the creative economy is 0.38 percent smaller than in 2023.